GREEN MAREKETING: AWARENESS AND PROSPECTS - Dr. Rituraj Pant; Surbhi Chugh (International Educational Journal of Science and Engineering, 2025)
Green marketing, or creating and advertising products that benefit the environment, has become a vital tactic for companies looking to meet the increasing demand from customers for environmentally friendly operations. The present status of green marketing is examined in this essay, with particular attention paid to consumer awareness and the opportunities for companies implementing green marketing tactics. The degree of consumer awareness of sustainable practices and green products is examined in the first section of the paper. A review of recent studies and surveys reveals that consumers’ awareness of environmental issues has significantly increased. The increased consciousness is fueling the market for environmentally friendly products that are openly advertised as such. The prospects for companies using green marketing techniques are covered in detail in the second section. In order to promote an open and efficient green marketing ecosystem, the paper asks for continued research and cooperation between stakeholders. The descriptive nature of this research paper is supported by secondary sources that were gathered from various publications, including books, websites, articles, and research papers.